Teaching Arabic Grammar Using the Textbook 'Al-‘Arabiyah Bayna Yadaik Series 4' at Ma'had Aly Ar Raayah - Sayid Munadi Siddiq; Laily Fitriani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The innovation of Arabic language learning has taken various forms, including the development of textbooks aimed at facilitating the learning process for students. One such innovative product is the 'Al-'Arobiyah Bain Yadaik' textbook, particularly its fourth series, which is utilized in qawaid learning at Ma'had Aly Ar Raayah. This study employs a descriptive qualitative research method with a focus on field research. The primary objective is to comprehensively delineate the qawaid learning process using the mentioned textbook, highlighting its advantages and disadvantages. The qawaid learning process involves apperception, linking new material with previous knowledge, followed by an explanation of the title, practical examples, and detailed rule formulation. An apparent advantage of utilizing 'Al-'Arobiyah Bain Yadaik' is the abundance of practical examples that facilitate student comprehension of the material. However, a notable drawback is the limited theoretical explanations, necessitating additional input from the teacher. This research serves as a valuable resource for institutions considering the adoption of 'Al-'Arobiyah Bain Yadaik' as a teaching material for qawaid lessons, providing insights into the learning process and offering recommendations for improvement